Upaya Peningkatan Spiritual Anak Anak Melalui Kegiatan Penelaahan Alkitab di Desa Tinada,Kabupaten Pakpak Bharat - bancin, wesli; Bancin, Wesli Edrianto; Berutu, Donni; Manik, Samuel Moi; Anakampun, Risden (PT Ruang Publikasi, 2024)
This activity is a form of community service as one of the three pillars of higher education which aims to help children not only understand the text of the Bible but also develop useful social and cognitive skills.The background of this study is the low access and facilities for religious activities that can support the spiritual development of children in the village. The methods used include organizing regular Bible study activities, involving children of various ages and mentoring by experienced facilitators. The results of the activities show that children's participation in Bible study has a significant positive impact on their spiritual development. Children experience an increase in their understanding of religious values, ethics, and morals, and show progress in aspects of character such as self-awareness, empathy, and responsibility. In addition, this activity also strengthens social relations between children and the local community, creating an environment that supports healthy spiritual growth.